KEANEKARAGAMAN VEGETASI DI KAWASAN HUTAN MANGROVE DESA NUSAPATI KABUPATEN MEMPAWAH - Prastomo, Ragil Hendro; Herawatiningsih, Ratna; Latifah, Siti (Universitas Tanjungpura, 2017)
Pontianak and Kubu Raya Regency have mangrove forest with an area about 178,845.14 ha or 37.86% and damage area about 80.76%. About 44.36% of mangrove forest has been severely damaged or light. This research aimed to know about the diversity of mangroves vegetation in Nusapati Village of Mempawah Regency. The results of this research is expected to provide information about the various types of vegetation diversity in mangrove forest in the Nusapati Village Mempawah Regency. This research was conducted at mangrove forest area in Nusapati Village of Mempawah Regency, West Kalimantan Province. This research and data analysis was conducted from 6 to 27 August 2016 (about 4 weeks). Technique of sampling was taken by using survey method whereas determination of the sampling was conducted by using purposive sampling, which means that the plot of research is placed in accordance with the discovery of mangrove trees in the forest area. Vegetation analysis in this research is made 17 lines which each of track has a length of 200 meters. The result of vegetation analysis showed that there were 11 types of vegetation that is consisting of 6 genus which is Aegiceras, Avicennia, Bruguiera, Excoecaria, Soneratia and Xylocarpus, and the others kinds that is founded are Aegiceras floridum, A. alba, A. lanata, A. marina,Â B. cylindrica, B. gymnorrhiza, B. parviflora, E. agallocha, S. alba, S. caseolaris, X. moluccensis. The diversity of genus that was founded in mangrove forest Nusapati Village Mempawah Regency, there needs to be further research to find out another types that has not been inventorying. Keywords:, Important Value Index, Mangrove Forest, Nusapati Village, Purposive Sampling, Vegetation Analysis